Postzygotic HRAS and KRAS mutations cause nevus sebaceous and Schimmelpenning syndrome - Groesser, Leopold; Herschberger, Eva; Ruetten, Arno; Ruivenkamp, Claudia; Lopriore, Enrico; Zutt, Markus; Langmann, Thomas; Singer, Sebastian; Klingseisen, Laura; Schneider-Brachert, Wulf; Toll, Agusti; Real, Francisco X; et al. (Nature genetics, 2012)
Christian Hafner and colleagues identify postzygotic HRAS and KRAS mutations as the cause of nevus sebaceous and Schimmelpenning syndrome. Their functional studies suggest that the HRAS p.Gly13Arg alteration, found in 91% of lesions, results in activation of the MAPK and PI3K-Akt signaling pathways. Nevus sebaceous is a common congenital cutaneous malformation. Affected individuals may develop benign and malignant secondary tumors in the nevi during life. Schimmelpenning syndrome is characterized by the association of nevus sebaceous with extracutaneous abnormalities. We report that of 65 sebaceous nevi studied, 62 (95%) had mutations in the HRAS gene and 3 (5%) had mutations in the KRAS gene. The HRAS c.37G>C mutation, which results in a p.Gly13Arg substitution, was present in 91% of lesions. Nonlesional tissues from 18 individuals had a wild-type sequence, confirming genetic mosaicism. The HRAS c.37G>C mutation was also found in 8 of 8 associated secondary tumors. Mosaicism for HRAS c.37G>C and KRAS c.35G>A mutations was found in two individuals with Schimmelpenning syndrome. Functional analysis of HRAS c.37G>C mutant cells showed constitutive activation of the MAPK and PI3K-Akt signaling pathways. Our results indicate that nevus sebaceous and Schimmelpenning syndrome are caused by postzygotic HRAS and KRAS mutations. These mutations may predispose individuals to the development of secondary tumors in nevus sebaceous.